Financial development and economic growth : (Routledge, 1996)
This volume brings together a colection of theoretical and empirical findings on aspects of financial development and economic growth in developing countries. It is divided into two main parts. The first identifies and analyses the major theoretical issues using examples from developing countries to show how these work in practice. This part addresses a wide range of topic issues, including endogenous growth and investment. The second part looks at the implications for financial policy in developing countries. Empirical evidence is again drawn from across a broad range of developing countries and regions